Vertical accuracy assessment of open access digital elevation models: Bucaramanga-Colombia case study - Aponte Saravia, Jhonathan (Geodesy and Cartography, 2022)
Digital Elevation Models (DEMs), are fundamental data that allow to represent topographic information continuously. They are widely used in various applications such as geoscience, and in the graphical representation of the landscape surface. Performing the analysis by using DEMs in which the real shape of the surface is adjusted, this would contribute significantly in obtaining their results as we would be approaching the actual occurrence of the object of study in the landscape. Currently, several global DEMs are freely available. However, various investigations have produced different results, so there are uncertainties as to which model is more appropriate for some areas. In that sense, the research was aimed at comparing the vertical accuracy of four DEMs in the city of Bucaramanga using central tendency statistical methods such as mean analysis, standard deviation and root mean squared error. As a result, the model that showed the best vertical accuracy was the one generated by the Advanced Land Observation Satellite program – Synthetic Aperture Radar and X-band Shuttle Radar Topography Mission, with a root mean squared error of 8.22 and 8.55 m respectively. Moreover, the one that best represented the shape of the landscape was the X-band Shuttle Radar Topography Mission X model.